1994
DOI: 10.1016/0735-1097(94)90590-8
|View full text |Cite
|
Sign up to set email alerts
|

Relation between procedural activated coagulation time and outcome after percutaneous transluminal coronary angioplasty

Abstract: A diminished activated coagulation time response to an initial bolus of heparin is associated with major in-hospital complications after coronary angioplasty, although patients with complications did have a higher risk before the procedure. It remains to be determined whether there is an ideal "target" activated coagulation time for interventional procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(57 citation statements)
references
References 13 publications
2
53
0
2
Order By: Relevance
“…Whereas some studies have identified an inverse relationship between the initial ACT and the risk of ischemic events (733,734), others found either no relationship or a direct relationship between the degree of anticoagulation and occurrence of complications (735 (748)(749)(750).…”
Section: Tirofibanmentioning
confidence: 99%
“…Whereas some studies have identified an inverse relationship between the initial ACT and the risk of ischemic events (733,734), others found either no relationship or a direct relationship between the degree of anticoagulation and occurrence of complications (735 (748)(749)(750).…”
Section: Tirofibanmentioning
confidence: 99%
“…[37][38][39] These methods are considered the standard of care during cardiopulmonary bypass and percutaneous coronary interventions, and they are rapidly gaining acceptance in ambulatory practices to expedite decision making and to avoid prolonged delays (and patient dissatisfaction) awaiting the results from central laboratories.…”
Section: Monitoring Global Coagulationmentioning
confidence: 99%
“…During angioplasty, values Ͻ250 seconds are associated with an increased incidence of major complications. 37 Administration of the platelet glycoprotein IIb/IIIa inhibitor abciximab prolongs the ACT by Ϸ35 seconds. 38 …”
Section: Activated Partial Thromboplastin Timementioning
confidence: 99%
“…4 This recommendation is based on data from retrospective analyses showing an association between ACT values and thrombotic 5,6 or bleeding 7 outcomes. However, these observational studies are subject to confounding, and they were conducted before the availability of modern antiplatelet therapy and, for some studies, before the widespread use of coronary stents.…”
mentioning
confidence: 99%
“…2 Because UFH has a narrow therapeutic window and its effect is poorly predictable, 3 guidelines from the United States recommend UFH dosing guided by measurement of activated clotting time (ACT) in the catheterization laboratory. 4 This recommendation is based on data from retrospective analyses showing an association between ACT values and thrombotic 5,6 or bleeding…”
mentioning
confidence: 99%